The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/jee/toz221
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Field Validation of a Beta-cyfluthrin-Based ‘Attract-and-Kill’ Device for Suppression of Asian Citrus Psyllid (Hemiptera: Liviidae) on Residential Citrus

Abstract: An ‘attract-and-kill’ (AK) device was evaluated for suppression of adult Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), on residential citrus. The AK device, made from weather-resistant plasticized PVC, lured D. citri adults by simulating the color of citrus flush and killed them with beta-cyfluthrin. This study evaluated: 1) lethality of AK devices weathered up to 8 wk on residential citrus; 2) survival of psyllids caged with potted plants and AK devices; 3) psyllid suppression achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Attract-and-kill devices or traps based on psyllid visual and gustatory behavior could be a valuable addition to practices currently available for management of D. citri 48 . Traps combining yellow color (long-range wavelength) with UV (short-range wavelength) reflectance from magnesium oxide should provide an effective combination of visual cues to promote both long-range attraction and sustainted probing behavior by psyllids.…”
Section: Discussionmentioning
confidence: 99%
“…Attract-and-kill devices or traps based on psyllid visual and gustatory behavior could be a valuable addition to practices currently available for management of D. citri 48 . Traps combining yellow color (long-range wavelength) with UV (short-range wavelength) reflectance from magnesium oxide should provide an effective combination of visual cues to promote both long-range attraction and sustainted probing behavior by psyllids.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chow et al 2019 [6] reported suppression of D. citri with an 'attract-and-kill' (AK) device that combined visual cues with a pyrethroid toxicant (β-cyfluthrin). Building upon these results, we developed two AK device prototypes that incorporated multiple sensory cues known to affect host finding and probing behaviors of D. citri, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Diaphorina citri has only emerged as a pest insect in the USA in the last decade and more immediate tools such as synthetic insecticides were initially sought out to overcome the impending panzootic, especially in commercial citrus (Grafton-Cardwell 2006). More recently, however, attention has turned to smaller, less managed citrus groves and residential citrus (Se ´tamou et al 2020;Chow et al 2019). This has created a niche demographic of individuals who would prefer not to use synthetic insecticide control methods and keep their citrus trees and residences organic, or at the least free of pesticide residues.…”
Section: Introductionmentioning
confidence: 99%